Teacher Responses to Curriculum Changes at the Elementary Education Level - Syafrilian Akemza; Milda Aisyah Furi; Wahid Murni; Samsul Susilawati (JURNAL ASIMILASI PENDIDIKAN, 2026)
The change in the curriculum is an effort by the government to improve the quality of education and adapt the learning process to the demands of the times. Implementation of an Independent Curriculum as an improvement. The 2013 curriculum demands readiness as well as teacher adaptation to carry out learning. This research aims to describe teachers' responses to changes in the curriculum at the education level. The research uses a qualitative approach with a descriptive qualitative design. Data were obtained through in-depth interviews with the head of the school and teachers with long and short service periods, and were supported by study documentation. Data analysis uses the interactive model of Miles, Huberman, and Saldana, which includes data reduction, data presentation, and withdrawal. Conclusion and verification. Research results show that teachers' responses to the 2013 Curriculum regarding the Independent Curriculum are diverse and influenced by teaching experience. Teachers with long tenure tend to experience challenges in adapting to the paradigm of learning. Meanwhile, teachers with shorter work periods show greater openness to change because they have more space to innovate in learning. Support from the school through training, mentoring, and strengthening collaboration among teachers is an important factor in the successful implementation of the Independent Curriculum. Findings from the study show that collaboration between teachers and experience with different teaching practices can strengthen the adaptation process to curriculum changes at the elementary education level.